2019
DOI: 10.1136/bmjopen-2019-029641
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with long-term prescription of benzodiazepine: a retrospective cohort study using a health insurance database in Japan

Abstract: ObjectivesCurrent clinical guidelines discourage long-term prescription of benzodiazepines and Z-drugs (BZD); however, the practice continues to exist. The aim of this study was to investigate the proportion of long-term BZD prescriptions and its risk factors.DesignRetrospective cohort study using a health insurance database.SettingJapan.ParticipantsA total of 86 909 patients were identified as outpatients aged 18 to 65 years who started BZD between 1 October 2012 and 1 April 2015. After excluding patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 21 publications
4
34
1
Order By: Relevance
“… 20 Previous studies have mainly assessed long-term BZDR use in prevalent users, whereas this study population included only incident BZDR users. Previous studies assessing new BZDR users have found that the incidence of long-term use is 11.8% in the general population, 33 9% among working-aged persons (requiring longer use periods of ≥8 months without gaps), 34 26% among older adults, 35 22% among persons with bipolar disorder, 29 and 30% among older persons with Alzheimer disease. 36 All of these estimates are lower than the 39.4% incidence reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Previous studies have mainly assessed long-term BZDR use in prevalent users, whereas this study population included only incident BZDR users. Previous studies assessing new BZDR users have found that the incidence of long-term use is 11.8% in the general population, 33 9% among working-aged persons (requiring longer use periods of ≥8 months without gaps), 34 26% among older adults, 35 22% among persons with bipolar disorder, 29 and 30% among older persons with Alzheimer disease. 36 All of these estimates are lower than the 39.4% incidence reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Many psychiatric disorders can have anxiety and insomnia symptoms (i.e., mood disorders, such as major depressive disorder (MDD), and anxiety disorders, such as generalized anxiety disorder (GAD)), and BZD/Z can alleviate these disabling symptoms 36 . Excessive and long‐term use of BZD have been found to be associated with psychiatric illnesses, such as MDD, anxiety disorders (such as GAD) and neuroticism 37–40 . It can be understood that BZD consumption is a severity marker of the underlying illness.…”
Section: Discussionmentioning
confidence: 99%
“…36 Excessive and long-term use of BZD have been found to be associated with psychiatric illnesses, such as MDD, anxiety disorders (such as GAD) and neuroticism. [37][38][39][40] It can be understood that BZD consumption is a severity marker of the underlying illness. In the same way, substance abuse is a well-known complication of anxiety disorder and mood disorder.…”
Section: Articlementioning
confidence: 99%
“…11 However, the prolonged use of BZD is common in the United States, 12 England, 13 France, 14 Germany, 15 and other areas of the world, 16 and has led to a serious public health problem. This worldwide dilemma is related to a series of factors, including demographic factors, 14 treatmentrelated factors, 17 psychological factors, 17 personalityrelated factors, 18 and some other factors. 19 Until now, the research community has not paid sufficient attention to the prolonged use of BZD in post-stroke insomniacs.…”
Section: Introductionmentioning
confidence: 99%
“…We selected these observation factors based on previous literature related to the prolonged use of BZD in other populations, post-stroke insomnia, 15,[17][18][19]38 and our own clinical practice.…”
mentioning
confidence: 99%